AUGMENTING PUBLIC RELATIONS an introduction to ai and other technologies for pr - Phillips, David 1914- (CRC PRESS, 2024)
Augmenting Public Relations examines how existing technologies used in Public Relations (PR) are being significantly augmented because of the advent of Artificial Intelligence (AI). The book describes the opportunities and pitfalls of AI, recent and emerging technologies, and projections in their development, offering an introduction to practitioners on how they, too, can create their own AI-enhanced tools. The developments in augmented, virtual and meta-reality, aided by AI, have now become serious contenders for commercial communication, and the ability to harness this visual capability is explained in some detail. As is the ability for practitioners to automatically monitor and feed websites using Application Programming Interfaces (APIs). The book also considers computer games as a form of communication, and the evolving application of games supported by AI. In recent years, the PR monitoring industry has deployed AI to search for content of interest to clients across a vast range of media. It throws up huge amounts of data to be managed. The book explores how such resources can be harnessed for intelligence gathering and activity deployment in easy-to-understand language. The book also covers a range of other activities from brain to computer communication' to chatbots, including applications used by the Internet of Things, Security Issues and Crisis Management, and the crucial subject of Ethics. Examining a range of new practices for the PR industry, and covering both principles and applications, this book will be of great value to students, academics and practitioners alike.
Keywords: Public relations; Public relations -- Data processing; Relations publiques; Relations publiques; Informatique; public relations; COMPUTERS / Virtual Reality; BUSINESS & ECONOMICS / Public Relations